2014
DOI: 10.1155/2014/389257
|View full text |Cite
|
Sign up to set email alerts
|

Clinicohematological Study of Thrombocytosis in Children

Abstract: Introduction. Primary thrombocytosis is very rare in children; reactive thrombocytosis is frequently observed in children with infections, anemia, and many other causes. Aims and Objectives. To identify the etiology of thrombocytosis in children and to analyze platelet indices (MPV, PDW, and PCT) in children with thrombocytosis. Study Design. A prospective observational study. Material and Methods. A total of 1000 patients with thrombocytosis (platelet > 400 × 109/L) were studied over a period of 2 years. Plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
2
18
2
1
Order By: Relevance
“…Ozcan described upper respiratory tract infection as the most common cause of reactive thrombocytosis followed by pneumonia (4). Subramaniam et al, indicated that respiratory infection was the predominant (28.3%) infectious cause of reactive thrombocytosis (5). Hadidopulou found reactive thrombocytosis in children with viral respiratory tract infection (6).…”
Section: Introductionmentioning
confidence: 99%
“…Ozcan described upper respiratory tract infection as the most common cause of reactive thrombocytosis followed by pneumonia (4). Subramaniam et al, indicated that respiratory infection was the predominant (28.3%) infectious cause of reactive thrombocytosis (5). Hadidopulou found reactive thrombocytosis in children with viral respiratory tract infection (6).…”
Section: Introductionmentioning
confidence: 99%
“…The potential underlying causes include acute bacterial or viral infections, tissue damage, cancer and chronic inflammation, particularly during early life 2 3 . The most frequent cause of ST is respiratory tract infections (RTIs) in childhood; RTIs account for 60–80% of ST cases 4 5 6 . However, reports of thrombocytosis induced by viral infections are scarce, particularly in children.…”
mentioning
confidence: 99%
“…Iron deficiency is most commonly associated with thrombocytosis [57,58]. Elevated platelet counts, especially in the setting of iron deficiency, can lead to an increased thromboembolic risk, with clinical consequences especially in patients with inflammatory bowel disease, chronic kidney disease or cancer [59].…”
Section: Discussionmentioning
confidence: 99%